2009
DOI: 10.1021/es802930x
|View full text |Cite
|
Sign up to set email alerts
|

Emissions Inventory of PM2.5 Trace Elements across the United States

Abstract: This paper presents the first National Emissions Inventory (NEI) of fine particulate matter (PM 2.5 ) that includes the full suite of PM 2.5 trace elements (atomic number >10) measured at ambient monitoring sites across the U.S. PM 2.5 emissions in the NEI were organized and aggregated into a set of 84 source categories for which chemical speciation profiles are available (e.g., Unpaved Road Dust, Agricultural Soil, Wildfires). Emission estimates for ten metals classified as Hazardous Air Pollutants (HAP) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
237
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 256 publications
(254 citation statements)
references
References 20 publications
11
237
0
2
Order By: Relevance
“…Christian et al (2010) reported emissions of 17 metals from source measurements of open trash burning, of which antimony (Sb) was the most unique, consistent with a previous report at the USMexico border (Garcia et al, 2006). Fine particle Sb may be a useful tracer for PM 2.5 from this source in the MCMA, although this topic requires further research as many other Sb sources also exist (Reff et al, 2009). Christian et al (2010 also reported on the emissions from brick kilns, charcoal kilns, and cooking fires.…”
Section: Primary Inorganic Aerosolssupporting
confidence: 57%
“…Christian et al (2010) reported emissions of 17 metals from source measurements of open trash burning, of which antimony (Sb) was the most unique, consistent with a previous report at the USMexico border (Garcia et al, 2006). Fine particle Sb may be a useful tracer for PM 2.5 from this source in the MCMA, although this topic requires further research as many other Sb sources also exist (Reff et al, 2009). Christian et al (2010 also reported on the emissions from brick kilns, charcoal kilns, and cooking fires.…”
Section: Primary Inorganic Aerosolssupporting
confidence: 57%
“…Previous investigators have suggested at least five hypotheses to explain the wintertime PM other overpredictions Mathur et al, 2008b), and efforts are underway to test them. For example, Reff et al (2009) recently developed an anthropogenic emissions inventory for PM 2.5 trace elements (e.g., Fe, Ni, Zn) for the US. The CMAQ model will be modified to track several of those trace elements so that the resulting modeled values can be compared against measurements at the national monitoring networks.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Trace components were determined by multiplying trace elemental abundances by an oxygen to mental ratio (except for Al, Si, Ca, K, Fe and Ti). Each ratio of the element is obtained from Reff et al (2009) based on the most common oxidation states of metals. (3) Organic matter (OM) was calculated by multiplying OC abundance by ratio of OM/OC.…”
Section: Methodology For Establishing Source Profiles Data Quality Comentioning
confidence: 99%